STRENGTHENING RELIGIOUS EDUCATION AS THE IMPLEMENTATION OF CHARACTER EDUCATION IN DUWET KRAJAN VILLAGE - Tomy Rizky Izzalqurny; Alfi Rosyidah Hamim; Faridah Puteri Permatasari; Ahmad Hikami (Universitas Airlangga, 2022)
Juvenile delinquency is a social problem in Indonesia that still requires special attention. Character education is a solution to this problem. The purpose of character education is so that the individual is not affected by bad things so that he is able to join the community. The formation of children's character can be realized strategically through religious education. However, religious education held in schools has not been effective, so a Quran Education Park (TPQ) is needed. The MBKM Village Building Program implemented by the State University of Malang is a form of community service. The service activity was carried out at Mr. Mahsun's house which held TPQ for children in Duwet Krajan Village, Tumpang District. The activity will be held from November 2021 to December 2021. The activity starts at 14.00 until it is finished with a target of 60 children. The activity was carried out by helping the Koran activities and telling children one of the prophet's exemplary stories in easy-to-understand language so that children were able to take moral messages. This activity is carried out with the hope of instilling character education in children in Duwet Krajan Village.